Vehicle dynamics - Dukkipati, Rao V. (Narosa Publishing House, 2000)
The book appropriate for engineers researchers, and managers in ground transportation industry, urban rapid transit industry, urban rapid transit industry transport equiment manufacturing industry, transport technology research and development organizations and transportation regulatory agencies. The book provides a sound basic background for solving many prcatical vehicle dynamics problems or for pursuing more advanced or specialized studies. The book can also be used as a textbook for engineering courses in transport technology for senior undergraduate in introductory graduate students